IES Proposed Revisions: Takeaway Lessons to Enhance International Accounting Education Standards Convergence - Limijaya, Amelia (Universitas Pendidikan Indonesia, 2020)
International accounting education standards convergence is an important issue as it enhances the global accountancy profession’s competency and public trust to the profession. This paper attempts to conduct an analysis on IES 2, 3, 4 and 8 proposed revisions and the comment letters received from various respondents, to contribute to the IAESB’s effort in improving international accounting education standards convergence across jurisdictions. A content analysis approach is applied to the proposed revisions as well as the submitted comment letters, then discussions are provided based on the result of analysis and relevant literatures on the field. Analysis on comment letters reveals some recurring comments from respondents that need to be addressed by the board. In addition, a demographical-related analysis on comment letters also discloses several issues. Recommendations are given for the IAESB to gain its legitimacy and for academics to participate more in an effort to promote international accounting education standards.